A Sensitive Spectrophotometric Determination of Ritodrine, Pentazocine, Isoxsuprine Hydrochlorides and Amoxicillin in Pure and Pharmaceutical Samples. Issue 1 (2008) - Revanasiddappa, H. D.; Veena, M. A.
Abstract : A simple, accurate and highly sensitive spectrophotometric method for the determination of ritodrine hydrochloride (RTH), pentazocine hydrochloride (PZH), isoxsuprine hydrochloride (ISH) and amoxicillin (AMX) is described. The method is based on the oxidation of the studied drugs by a known excess of chloramine – T (CAT) in hydrochloric acid medium and subsequent determination of the unreacted oxidant by reacting it with iodide in the same acid medium liberates iodine, which subsequently react with starch to form a stable starch-iodine complex. The reacted oxidant corresponds to the drug content. The coloured complex exhibits a maximum absorption at 590 nm. The apparent molar absorptivity values and Sandell's sensitivity values are in the range 6.96x10 4 - 1.43x10 5 L mol –1 cm –1 and 2.45-4.30 ng cm –2, respectively. The method was successfully applied to the studied drugs in their dosage forms. The results are reproducible within ±1% and compare favorably with those of official methods of British Pharmacopoeia and the United States Pharmacopoeia.